The real exchange rate of an oil exporting economy: Empirical evidence from Nigeria - Hassan Suleiman; Zahid Muhammad (FIW - Research Centre International Economics, 2011)
In this study the long-run relationship between real oil price, real effective exchange rate and productivity differentials is examined using annual data for Nigeria over the period 1980 to 2010. We aim to investigate whether oil price fluctuations and productivity differentials affect the real effective exchange rate. The empirical results suggest that whereas real oil price exercise a significant positive effect on the real exchange rate in the long run. Productivity differentials exercise a significant negative influence on the real exchange rate. The study noted that, the real exchange rate appreciation of 2000-2010 was driven by oil prices. The findings of this study have important implications for exchange rate policy and are relevant to many developing economies where oil exports constitute a significant share of their exports.
Keywords: F31; C22; 330; Exchange rate; oil price; Nigerian economy